A chimeric repressor of petunia PH4 R2R3-MYB family transcription factor generates margined flowers in torenia. (3rd May 2016) - Kasajima, Ichiro; Sasaki, Katsutomo
ABSTRACT: The development of new phenotypes is key to the commercial development of the main floricultural species and cultivars. Important new phenotypes include features such as multiple-flowers, color variations, increased flower size, new petal shapes, variegation and distinctive petal margin colourations. Although their commercial use is not yet common, the transgenic technologies provide a potentially rapid means of generating interesting new phenotypes. In this report, we construct 5 vectors which we expected to change the color of the flower anthocyanins, from purple to blue, regulating vacuolar pH. When these constructs were transformed into purple torenia, we unexpectedly recovered some genotypes having slightly margined petals. These transgenic lines expressed a chimeric repressor of the petunia PhPH4 gene under the control of Cauliflower mosaic virus 35 S RNA promoter. PhPH4 is an R2R3-type MYB transcription factor. The transgenic lines lacked pigmentation in the petal margin cells both on the adaxial and abaxial surfaces. Expressions of Flavanone 3-hydroxylase ( F3H ), Flavonoid 3′-hydroxylase ( F3′H ) and Flavonoid 3′5′-hydroxylase ( F3′5′H ) genes were reduced in the margins of these transgenic lines, suggesting an inhibitory effect of PhPH4 repressor on anthocyanin synthesis.